Development of a Web-Based Research and Community Service Management System Using ISO 25010 Quality Standards - Efendi, Rizal; Aini, Nuru; Wijaya, Etistika Yuni; Maghfirli, Fadli (EDUTIC, 2025)
Research and community service data management is a vital component of higher education accreditation and strategic planning. However, the Informatics Education Study Program currently relies on manual documentation, resulting in data fragmentation and difficulties in mapping lecturers' research roadmaps. This study aims to develop a research management information system to digitize and integrate these processes, and to evaluate its technical feasibility. Using the Research and Development (RD) method with the Waterfall development model, software quality was tested based on the ISO 25010 standard, focusing on functional suitability, performance efficiency, and usability. The test results showed that the system had 100% functional suitability, a usability level of 92% (Very Good category), and performance efficiency with an average load time of 0.9 seconds. These findings confirm that the proposed system not only addresses the limitations of manual archiving but also significantly improves the effectiveness of academic data governance. This study contributes to providing a validated information system framework for intellectual asset management at the study program level.